2022
DOI: 10.2196/27735
|View full text |Cite
|
Sign up to set email alerts
|

Attrition Within Digital Health Interventions for People With Multiple Sclerosis: Systematic Review and Meta-analysis

Abstract: Background Digital health interventions have revolutionized multiple sclerosis (MS) care by supporting people with MS to better self-manage their disease. It is now understood that the technological elements that comprise this category of digital health interventions can influence participant engagement in self-management programs, and people with MS can experience significant barriers, influenced by these elements, to remaining engaged during a period of learning. It is essential to explore the in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Before commencing online course development, a systematic review and meta-analysis of RCTs (n = 32) describing digital health self-management interventions for plwMS was conducted to inform likely participant attrition. The pooled attrition rates for the intervention and control arms were 14.7% and 15.6%, respectively [ 72 ], demonstrating no significant difference in attrition between groups. A second systematic review and meta-analysis of RCTs of lifestyle interventions in other chronic diseases found no evidence of differential attrition between intervention and control arms, increasing confidence in conducting such studies with minimal potential of attrition bias [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Before commencing online course development, a systematic review and meta-analysis of RCTs (n = 32) describing digital health self-management interventions for plwMS was conducted to inform likely participant attrition. The pooled attrition rates for the intervention and control arms were 14.7% and 15.6%, respectively [ 72 ], demonstrating no significant difference in attrition between groups. A second systematic review and meta-analysis of RCTs of lifestyle interventions in other chronic diseases found no evidence of differential attrition between intervention and control arms, increasing confidence in conducting such studies with minimal potential of attrition bias [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews, such as Bevens et al [ 54 ], focused on the analysis of attrition of digital strategies in people with multiple sclerosis and found no significant differences between dropout rates in participants allocated to digital or control interventions. Although our findings are in line with these previous findings, the target population and research conditions differed from ours, so comparison of findings are difficult.…”
Section: Discussionmentioning
confidence: 99%
“…This idea is supported by the prediction intervals, which stated that our findings could change with future trials. The recent systematic review of Bevens et al ( 2021 ) analysed the dropout rate in people with multiple sclerosis who received digital health interventions, showing no significant differences between experimental and control comparators. Therefore, we can consider that the adherence to virtual reality or other technological approaches were at least similar to other interventions.…”
Section: Discussionmentioning
confidence: 99%